Psychiatric comorbidities in hoarding disorder: a structured clinical interview study - Nami Nishida; Keitaro Murayama; Hirofumi Tomiyama; Kenta Kato; Kang Mingi; Kou Matsukuma; Makoto Kawahito; Kana Tsunoda; Takuro Kamio; Ayaka Shuto; Tomohiro Nakao (Frontiers in Psychiatry, 2026)
Objective Hoarding disorder (HD) is a psychiatric condition characterized by persistent difficulty in discarding possessions, leading to significant clutter and functional impairment. HD is often comorbid with other psychiatric disorders, but previous findings of these comorbidities are inconsistent due to limited structured assessments. This study investigates the psychiatric comorbidities in individuals with HD using structured, clinician-administered interviews. Methods Between 2016 and 2022, 68 individuals diagnosed with HD were recruited from an outpatient clinic at Kyushu University Hospital. Comorbid psychiatric disorders were assessed using the Structured Clinical Interview for DSM, Conners’ Adult Attention-deficit/hyperactivity disorder (ADHD) Diagnostic Interview, and additional standardized scales. Demographic, clinical, and diagnostic data were collected. Results Eighty percent of the participants had at least one comorbid psychiatric disorder. ADHD was the most common comorbid disorder, occurring in 29.4% of the participants (95% confidence interval [CI], 18.6–40.3), followed by obsessive-compulsive disorder in 26.5% (95% CI, 16.0–36.9) and major depressive disorder in 20.6% (95% CI, 11.2–30.7). Among the participants with ADHD, 55% had the predominantly inattentive presentation and 45% had the combined presentation; none had the predominantly hyperactive-impulsive presentation. Conclusion The most common comorbidity associated with HD is ADHD. The significance of this study lies in the fact that a structured interview with a clinician was also used to diagnose ADHD; we believe that identifying comorbidities in HD will allow future research to better understand the related clinical features, neuropsychological testing, and imaging studies.